Undifferentiated Spondyloarthropathies in Brazilians: Importance of HLA-B27 and the B7-CREG Alleles in Characterization and Disease Progression - Sampaio-Barros, Percival D.; Conde, Roseneide A.; Donadi, Eduardo A.; Kraemer, Maria Helena S.; Persoli, Ligia; Coimbra, Ibsen B.; Costallat, Lilian Teresa L.; Samara, Adil M.; Bértolo, Manoel B. (My University, 2003)
Objective. To analyze the profile of the HLA-B27 and B7 cross-reactive group (CREG) alleles and the role of these markers in disease characterization and progression in patients with undifferentiated spondyloarthropathies (uSpA). Methods. A total of 80 patients with a diagnosis of uSpA (40 HLA-B27 positive and 40 HLA-B27 negative) were prospectively studied for 2 years. The control group consisted of 66 HLA-B27 positive and 112 HLA-B27 negative individuals without a history of seronegative SpA. HLA-B alleles were typed at low (B7-CREG alleles, i.e., B*7, B*54, B*55, B*56, B*40, B*42) or high resolution (B*27 alleles) using polymerase chain reaction-amplified DNA hybridized with sequence-specific oligonucleotide probes. Results. HLA-B*2705 was the most frequent allele, observed in 92.5% of the patients and in 77% of the controls, followed by the HLA-B*2702, observed in 5% of the patients and in 12% of the controls. HLA-B*2704 was observed in only one patient (2.5%), and was absent in the control population. HLA-B*2703 (6%) and HLA-B*2707 (5%) alleles were observed only in controls. No associations between HLA-B*27 alleles or B7-CREG alleles and any specific manifestation of uSpA were observed. HLA-B27 positive patients more frequently presented juvenile onset SpA (p = 0.002) and progression to ankylosing spondylitis (AS) (p = 0.03) than did HLA-B27 negative patients. The B7-CREG alleles were observed in 5% of the HLA-B27 positive uSpA group, in 25% of the HLA-B27 negative uSpA group, in 7% of the HLA-B27 positive controls, and in 13% of the HLA-B27 negative controls; a significant association was observed between the presence of the B7-CREG and the HLA-B27 negative uSpA group (p = 0.012). Conclusion. The frequency of the HLA-B*2705 allele among the B27 positive uSpA patients of this series was closely similar to that reported for patients with ankylosing spondylitis (AS). The presence of HLA-B*27 alleles was associated with the progression to AS, and the presence of B7-CREG was associated with uSpA in the HLA-B27 negative group.
Keywords: Alleles; Followup; HLA-B27; Spondyloarthropathies; Undifferentiated spondyloarthropathies